Questioning the Authority of Converts' Preaching: A Critical Discourse Analysis of Sidogiri Media Edition 211 - Muhammad Hafid Yasuli; Siti Raudhatul Jannah; Kun Wazis (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2026)
This study aims to analyze how Sidogiri Media, as a pesantren media, represents the discourse of the authority of converts' da'wah in its 211th edition entitled "Converts Preach, Isn't It Dangerous?" This study uses a qualitative approach with a library research type and applies Teun A. van Dijk's Critical Discourse Analysis model which includes three main dimensions: text structure, social cognition, and social context. The results show that Sidogiri Media frames the phenomenon of converts' da'wah as an issue that needs to be controlled and directed by religious scholars, especially pesantren. Through evaluative diction, instructive sentences, and contrasting patterns between "those with knowledge" and "those who are just learning," this bulletin emphasizes the position of pesantren as a scientific authority and guardian of the legitimacy of Islamic da'wah. From a social cognition perspective, the author's view is influenced by traditional pesantren values that uphold sanad and knowledge as the basis of da'wah authority, while from a social context, this text is a form of pesantren's ideological response to the disruption of religious authority in the digital era. Thus, Sidogiri Media not only functions as a medium for preaching, but also as a means of reproducing Islamic boarding school ideology in maintaining the structure of religious authority in the Islamic public sphere.